Hyper ige syndrome associated with novel dock8 heterozygous mutation: а case report - D. V. Osypchuk; A. M. Hilfanova (Group of Companies Med Expert, LLC, 2020)
Dedicator of cytokinesis 8 (DOCK8) deficiency is an autosomal recessive combined immunodeficiency within the spectrum of hyper-IgE syndromes. Here we report a patient with a novel heterozygous mutation in DOCK8 gene associated with a clinical presentation of hyper-IgE syndrome (HIES). A case report. The patient presented with severe congenital atopic dermatitis, allergic rhinitis and bronchial asthma which was developed during the 3rd year of life. Also, the patient suffered from recurrent otitis and lymphadenopathy of the inguinal lymph nodes. The immune evaluation showed normal lymphocytes subpopulation and increased serum IgE - 32.131 ІU/L. Genetic sequencing revealed a heterozygous defect c.5266A>T (p.Ile1756Phe) in the DOCK8 gene. Therapy with omalizumab was started and a significant improvement of skin syndrome was achieved. Conclusions. Our data and therapeutic approach may be clinically useful as the diagnostic and treatment approach for severe atopic dermatitis that does not fit the full criteria for previously reported hyper-IgE syndromes. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of all participating institution. The informed consent of the child's parents was obtained from the studies.No conflict of interest was declared by the authors.